The Production of “Breakout” and “Kimchi” Talk Show Program at Pro 2 RRI Semarang (Program director) - Tsalitsati, Afiati; Ratri Rahmiaji, M.Si, Dr. Lintang (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Radio Republik Indonesia is the oldest radio in Indonesia and the only government-owned radio that had the vision to realize the public broadcasters Indonesia as the largest networked radio, the character development of the nation, world class. RRI has a very extensive network from Aceh to Papua, but not many people, especially young people who are interested in listening to Radio Republik Indonesia. The main reason is the image of RRI as radio news and radio for the elderly, making it less attractive to young people. One solution is to create a talk show programs Breakout and Kimchi on RRI Pro 2 Semarang and targeting young people as the target audience. So it is expected to increase the radio listeners again, especially RRI Pro 2 Semarang, which has a target audience among the young. During the implementation of this program, the author has a duty to execute the event that appropriate with run down and concept that was created by the creative director and has been approved by the producer. Promotion using social media such as twitter, instagram, Line, whatsapp is carried out before and during the event. The questionnaire result of post-production shows through the talk show programs “Breakout” and “Kimchi” our main target is to increase the listener number of PRO 2 RRI Semarang are fulfilled.